The Existence of a Unique Solution of the Hyperbolic Functional Differential Equation - Karpowicz Adrian (Demonstratio Mathematica, 2014)
We consider the Z. Szmydt problem for the hyperbolic functional differential equation. We prove a theorem on existence of a unique classical solution and the Carathéodory solution of the hyperbolic equation.